Operaciones básicas y resolución de problemas matemáticos en la asignatura matemática de tercero de bachillerato general unificado, Colegio de Bachillerato 27 de Febrero, periodo 2021-2022 - Erreyes Cabrera, Evelyn Katherine (2022)
The purpose of this research was to describe how the correct application of basic operations helps improve the resolution of mathematical problems of third year high school students; considering that these skills contribute in areas such as entering to third level studies and the consolidation of logical thinking. It was methodologically based on a qualitative approach with a documentary character, therefore, the research is descriptive. The investigative techniques used were documentary review and survey; search logs, content sheets and the questionnaire were used as instruments. The main results indicate that students have difficulty solving mathematical exercises because they do not have well-grounded knowledge such as the hierarchy of operations and systematic order. Also, the degree of problem solving is at a low level, since the ability to reason with a logical sense has not been effectively developed in students. Key words: basic operations, problem solving, strategy, simulation and mathematical problems.